Development of Interactive Multimedia Based Mathematics Learning Media for Class XI SMA - Prasetyo, Hanif; Herfina, Herfina; Putra, Agung Prajuhana (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2024)
Mathematics is a science that studies quantity, structure, space and change. This science has abstract and universal study objects which play an important role in discipline and the development of human thinking power. The mathematical mindset is deductive, starting from general objects to important conclusions. Multimedia learning methods are an alternative to help students understand material concretely. The use of multimedia can make learning more interesting with graphics, animation, video and sound. Teachers must use approaches, methods and techniques that actively involve students in learning in order to achieve good academic achievement. The use of learning media can create new interests and motivate students. Developing mathematics learning media using Adobe Animate to create animations is an interactive learning media that can help teachers broaden students' horizons and increase student interest and motivation. Interactive multimedia-based learning can increase motivation, learning independence and be a solution to make mathematics learning interesting and easy to understand